Koncepcje prawnej podmiotowości przyrody - Rotko, Jerzy (PRAWO i WIĘŹ, 2025)
The purpose of the study is to present methods of introducing subjective rights of nature into the legal system, taking into account the legal solutions in force in selected countries. They consist of both statutory provisions (Ecuador) and case law (Colombia, India, Bangladesh, New Zealand). The discussion on the subjective rights of nature is not limited to their instrumental treatment, because in order to realize them it assumes the need for a profound transformation of the law through a change in the philosophical and legal paradigm. The initial premise of this process is the departure from the canon of anthropocentrically understood ethics. The legislative solutions adopted today, including constitutional ones, refer to human spirituality, animistic understanding of nature and religious beliefs. This confirms the fundamental importance of the cultural environment for legal debate. It can be concluded that in the Polish cultural and legal and political realities there is no justification for implementing the ideas of normative personification of nature understood in this way.